Multi-Dimensional Angle of Arrival Estimation by Circular Phased Adaptive Array Antennas - Mohammed, Bassim Sayed (Al-Khwarizmi Engineering Journal, 2017)
In this paper the use of a circular array antenna with adaptive system in conjunction with modified Linearly Constrained Minimum Variance Beam forming (LCMVB) algorithm is proposed to meet the requirement of Angle of Arrival (AOA) estimation in 2-D as well as the Signal to Noise Ratio (SNR) of estimated sources (Three Dimensional 3-D estimation), rather than interference cancelation as it is used for. The proposed system was simulated, tested and compared with the modified Multiple Signal Classification (MUSIC) technique for 2-D estimation. The results show the system has exhibited astonishing results for simultaneously estimating 3-D parameters with accuracy approximately equivalent to the MUSIC technique (for estimating elevation and azimuth angles), and it has privilege to estimate SNR for sources which are under the estimation process. Finally, the proposed system needs less computational time and hardware complexity when it is compared with Eigen value decomposition techniques used by MUSIC technique. Also, it has cost effectiveness with respect to (3-D) active detecting means such as radars.